Willingness to pay a premium for eco-label products in China: a mediation model based on quality value - Ying Zhan; Yuting Ren; Junfei Xu (Scientific Reports)
Abstract Sustainable consumption plays an important role in achieving sustainable development. Eco-labels can help to convey this message to consumers. In China, the new carbon label represents a new kind of sustainable eco-label; as such, the relationship between carbon labeling and consumers’ willingness to pay (WTP) a premium is worth studying. This paper explores the impact of carbon label recognition on WTP a premium, which is also affected by the perceived value of quality attributes and effective advertising campaigns. The results show that the former plays an intermediary role in carbon label recognition and premium payment intention, while the latter regulates the relationship between perceived value of quality attributes and premium payment intention. The research shows that when consumers are aware of carbon labeling, they are more willing to pay higher prices for products as they believe the quality of these products to be higher. For others, effective advertising campaigns can encourage paying a premium. This not only provides suggestions for enterprises promoting green products and for governments wishing to raise environmental awareness via guidance and education but also promotes the sustainable development of green products.